PCR with 5-methyl-dCTP replacing dCTP. - Wong, K K (1991)
When dCTP is replaced by methyl5-dCTP in the polymerase chain reaction some templates cannot be efficiently amplified by Taq polymerase or Vent polymerase using standard cycling parameters. However, this phenomenon can be overcome by increasing the temperature of the denaturation steps to 100 degrees C, or by adding dITP to destabilize the m5dC:dG base pairs. Once the block to amplification of m5dC-substituted DNA was overcome, methylated DNA from the 'superpolylinker' of the plasmid pSL 1180 was used as a substrate to check the methyl-sensitivity of a variety of restriction endonucleases. The m5dC-substituted DNAs should also be valuable substrates for defining the specificity of methyl-dependent endonucleases.